Islamic and Scientific Perspectives on Shading Coefficient, Carbon Dioxide Concentration Reduction, and Cooling Effect of Productive Facade - Noraduola, Dwi Rinnarsuri; Mangkoedihardjo, Sarwoko; Santoso, R. Irwan Bagyo; Purwanti, Ipung Fitri; Jaya, Laode M. Golok; Cahyadi, Rusli (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2025)
The concept of productive green space has been mentioned in Al-Qur’an, which was revealed several centuries ago. However, Productive Facade (PF), a Vertical Greening System (VGS) method, has only recently been seen as a viable solution to provide crops and a cooler atmosphere in densely populated residential areas. The purpose of this article is to examine, from both scientific and Islamic perspectives, how shading and CO2 concentration reduction from PF can help cool the outdoor air, as well as the implications of this cooling mechanism for the development of a PF system as a secondary building skin that is more responsive to increasing urban temperatures. Literature reviews and experimental studies have been conducted to provide evidence and arguments from both scientific knowledge and Islamic perspectives. It was found that PF was able to provide an outdoor cooling effect. In addition, plant shade and CO2 uptake in PF are strongly correlated with air temperature. These findings are mentioned in the Qur'an and Hadiths as a basis for constructing an Islamic perspective.